Antimicrobial peptide-loaded liquid crystalline precursor bioadhesive system for the prevention of dental caries - Aida, Kelly Limi [UNESP]; Kreling, Paula Fernanda [UNESP]; Caiaffa, Karina Sampaio [UNESP]; Calixto, Giovana Maria Fioramonti [UNESP]; Chorilli, Marlus [UNESP]; Spolidorio, Denise M. P. [UNESP]; Santos-Filho, Norival Alves [UNESP]; Cilli, Eduardo Maffud [UNESP]; Duque, Cristiane [UNESP] (Taylor & Francis, 2018)
Background: Anticaries agents must interfere with the adhesion of Streptococcus mutans and its proliferation in dental biofilm, without causing host toxicity and bacterial resistance. Natural substances, including cationic antimicrobial peptides (CAMPs) and their fragments, such as β-defensin-3 peptide fragment (D1-23), have been widely studied. However, the chemical and physical stability of CAMPs may be compromised by external factors, such as temperature and pH, reducing the period of antimicrobial activity. Methods: To overcome the aforementioned disadvantage, this study developed and characterized a drug delivery system and evaluated the cytotoxicity and effect against S. mutans biofilm of a D1-23-loaded bioadhesive liquid crystalline system (LCS). LCS was composed of oleic acid, polyoxypropylene-(5)-polyoxyethylene-(20)-cetyl alcohol, Carbopol® 974P and Carbopol® 971P. LCS was analyzed by polarized light microscopy (PLM), rheology (viscoelasticity and flow properties) and in vitro bioadhesion. The viability of epithelial cells was evaluated. Minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) against S. mutans were determined for D1-23 for further evaluation of the effect against S. mutans biofilm after 4 and 24 h of exposure to treatments. Results: PLM, rheology, and in vitro bioadhesion tests showed that both viscosity and bioadhesion of LCS increased after it was diluted with artificial saliva. D1-23-loaded LCS system presented better activity against S. mutans biofilm after 24 h when compared to 4 h of treatment, showing a cumulative effect. Neither LCS nor D1-23-loaded LCS presented toxicity on human epithelial cells. Conclusion: D1-23-loaded LCS is a promising drug delivery system for the prevention of dental caries.
Keywords: Biofilm; Dental caries; Drug delivery system; Peptide fragments; Streptococcus mutans